Resistance of common bean lines to Sclerotinia sclerotiorum isolates under different environmental conditions - Abreu, Mariana Junqueira de; Leite, Monik Evelin; Ferreira, Alex Naves; Pereira, Rafael; Pereira, Fernanda Aparecida Castro; Souza, Elaine Aparecida de (Pesquisa Agropecuaria Brasileira, 2022)
The objective of this work was to evaluate the reaction of common bean (Phaseolus vulgaris) lines to Sclerotinia sclerotiorum, the aggressiveness of the isolates, and the inheritance of resistance to white mold, under two environmental conditions. The experiments were carried out under field and greenhouse conditions. In each one, four isolates were inoculated in 14 common bean lines using the straw-test inoculation method and severity on plants. No common bean line with a high level of resistance to white mold was identified, and most of the lines were moderately resistant to the pathogen. In general, the BRS Campeiro, BRS Radiante, BRSMG Talismã, and Ouro Negro cultivars stand out for resistance. Under field conditions, the UFLA 3 isolate discriminates well the lines, while, under greenhouse conditions, UFLA 26 and UFLA 92 are the most aggressive isolates. Furthermore, according to the genetic study, most of the observed variation can be attributed to horizontal resistance, although a small part is associated with vertical resistance.
Keywords: Phaseolus vulgaris; diallel analysis; white mold.